An Operational System For Monitoring Oil Spills In The Mediterranean Sea: The PROMED System - KERAMITSOGLOU, I.; ASIMAKOPOULOS, D.N.; CARTALIS, C.; PETRAKIS, M.; ARGIRIOU, A.; KASSOMENOS, P.; THEOPHILOPOULOS, N.; NTZIOU, I.; HERRERO, A.M. (Mediterranean Marine Science, 2003)
The primary objective of this work was the development of an operational system for early detection of oil-spills, monitoring of their evolution, and provision of support to responsible Public Authorities during cleanup operations, based on Remote Sensing and GIS technologies. In case of emergency, the principal characteristics of the oil spill are defined with the aid of a space-borne synthetic aperture radar (SAR). The transport, spreading and dispersion of the oil spill is subsequently simulated on the basis of wind forecasts of the area. The use of thematic maps of protected, fishing and urban areas, and regions of high tourism allows the better assessment of the impact of an oil spill on the areas to be affected in terms of environmental sensitivity. Finally, reports are generated notifying port authorities, the media, and local organizations to be potentially affected by the presence of the oil spill. The pilot site for testing the PROMED System in Greece is the island of Crete.